Sports injury investigation and risk assessment of national female tennis players - Zhang, L.; Furjan-Mandic, G. (Science and Racket Sports VI, 2019)
For completing the requirements of reducing the injury rates for national female tennis players, we collect the information of sports injuries by questionnaire, carry out the ROM test and muscle length test to assess the risks of injury from 13 national female tennis athletes. Results: The national tennis players have a high rate of injuries, especially in wrist (28%), low back (23%), shoulder (17%), knee (15%) and so on, and the injuries in dominant side (49%) are more than the nondominant side (28%). Chronic injuries have the higher incidence than acute, mild is the most common injury degree, and moderate and long-term injuries are common. In the injury risk assessment, there are specific tennis changes in the muscle length and ROM, players have high injury risk in the assessment, indicating that injury is related to the changes in muscle and body structure caused by tennis training, the results help us to build the training system of prerehabilitation which providing the guidance for further training.